Molecular engineering of D–A–D conjugated small molecule nanoparticles for high performance NIR-II photothermal therapy. Issue 5 (5th February 2020) - Shao, Wei; Wei, Qiaolin; Wang, Shuaifei; Li, Fangyuan; Wu, Jiahe; Ren, Jiafeng; Cao, Fangyi; Liao, Hongwei; Gao, Jianqing; Zhou, Min; Ling, Daishun
Abstract : Highly efficient NIR-II photothermal therapy is enabled by molecularly engineered conjugated small molecule nanoparticles. Abstract : Chemically defined conjugated small molecules (CSMs) and their nanoparticles (CSMNs) have been widely used in phototheranostics. However, CSMNs have rarely been studied for second near-infrared (NIR-II) deep-tissue photothermal therapy (PTT) due to the lack of NIR-II-absorbing CSMNs. Herein, through a molecular engineering strategy of "increasing the number of thiophene bridges", three donor–acceptor–donor (D–A–D) CSMs, namely CSM0-2 in which the number represents the number of thiophene bridges, have been synthesized. The optical bandgap decreases with the increase of the number of thiophene bridges. Among them, CSM2 has strong absorption in both the first near-infrared (NIR-I) and NIR-II regions. CSMN2 exhibits high photothermal conversion efficiency (PTCE = 31.6%) in NIR-II and excellent biocompatibility. By using CSMN2, photoacoustic imaging (PAI)-guided in vivo tumor NIR-II PTT is achieved under low laser power density (0.5 W cm −2 ). The molecular engineering strategy reported here can potentially be applied to other D–A systems for the development of new materials in phototheranostics.